Occurrence of Microcerella halli (Engel) (Diptera, Sarcophagidae) in snake carrion in southeastern Brazil - Moretti, Thiago de C. [UNESP]; Allegretti, Silmara M.; Mello-Patiu, Catia A.; Tognolo, Alexandre M.; Ribeiro, Odair B.; Solis, Daniel R. [UNESP] (Soc Brasileira Entomologia, 2009)
Occurrence of Microcerella halli (Engel) (Diptera, Sarcophagidae) in snake carrion in southeastern Brazil. The occurrence of 27 second-instar larvae of the flesh fly Microcerella halli (Engel, 1931) (Diptera, Sarcophagidae) in a carcass of a snake usually called as Urutu, Bothrops alternatus (Dumeril, Bibron & Dumeril, 1854) (Serpentes, Viperidae, Crotalinae) is reported. The snake was kept in captivity in a snake farm in Morungaba, São Paulo state, Brazil. Descriptions of reptile carcass colonization by insects and general biological data of this flesh fly are scarce and this necrophagic behavior is described for the first time in literature.

A ocorrência de 27 larvas de segundo estádio do sarcofagídeo Microcerella halli (Engel, 1931) (Diptera, Sarcophagidae) em uma carcaça de urutu Bothrops alternatus (Duméril, Bibron & Duméril, 1854) (Serpentes, Viperidae, Crotalinae) é relatada. A cobra era mantida em cativeiro em um serpentário no município de Morungaba, estado de São Paulo, Brasil. Descrições de colonização de carcaças de répteis por insetos e dados gerais da biologia deste sarcofagídeo são escassos, e este comportamento necrófago é descrito pela primeira vez na literatura.
Ocorrência de Microcerella halli (Engel) (Diptera, Sarcophagidae) em uma carcaça de cobra no sudeste Brasileiro
Keywords: Flesh flies; fly colonization; forensic entomology; reptile carcass